Rape Myth Acceptance Reflects Perceptions of Media Portrayals as Similar to Others, but Not the Self - Elmore, Kristen C. (Violence against women, 2021)
Understanding the antecedents and consequences of rape myths is important for sexual assault prevention programming. We investigated whether general perceptions of media predict rape myth endorsement among community college students, a group with elevated sexual assault risk. Students who perceived greater similarity between people they know and people in media reported higher endorsement of rape myths that blame the victim and exonerate the accused. This relationship did not emerge for perceptions of one’s personal similarity to people in media, with the exception of men’s endorsement of myths exonerating male perpetrators.